Literature Review Tax Compliance and Tax Revenue: Analysis of Understanding Tax Regulations and Quality of Service - Wibowo, Setyo; Hapzi Ali (Dinasti Publisher, 2022)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews Determination of Compliance Level and Tax Revenue: Analysis of Understanding Tax Regulations and Service Quality, A Study of Human Resource Management Literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The result of this research library is that: 1) Understanding of Tax Regulations Affects Compliance Level; 2) Service Quality Affects Compliance Level; 3) Understanding of Tax Regulations Affects Tax Revenue; 4) Service Quality Affects Tax Revenue; and 5) Compliance Level affects Tax Revenue.